Conceptual model for the design of product systems (2016)
Based on the concepts of personalization, differentiation and variability, product systems are characterized and the conditions for their design are explored. In the analysis of literature,17 variables related to the design of product systems were identified, and used to develop a conceptual model. In order to validate this finding, a survey was applied to 57 experts in the field of design. By means of a factor analysis, variables are reduced and the underlying conceptual relationships are identified. As a result of the validation, three factors are identified: structure, coherence and order, which contain the variables that determine the attributes of the product systems. These findings support the conclusion that the origin of the design process of these systems is based on the analysis of consumers and the multiple uses given and experiences obtained from these products. Study boundaries are established and future research possibilities are outlined.